Klimt artwork: red-pigment material investigation by backscattering Fe-57 Mössbauer spectroscopy, SEM and p-XRF. Issue 2 (15th December 2017) - Lehmann, R.; Wengerowsky, D.; Schmidt, H. J.; Kumar, M.; Niebur, A.; Costa, B. F. O.; Dencker, F.; Klingelhöfer, G.; Sindelar, R.; Renz, F.
ABSTRACT: Material tests were performed on a rediscovered Klimt-artwork " Trompetender Putto ". We performed studies on the red colored spots, mainly taken from non-restored parts. MIMOS II Fe-57 Mössbauer spectroscopy (novelty in art-pigment analysis) mainly reveals haematite and crystallized goethite in red colors. Electron microscopy can identify various layers of the original and overpainting of an artwork. The number of layers fluctuates between three and four chemically painted areas. The portable X-ray fluorescence analysis enables to reduce the pigment list to containing mercury (cinnabar), lead, zinc, iron and titanium. Infrared-light-irradiation visualizes the different age of the pigments.